Stochastic modeling and forecasting of reservoir inflows a case study in the Philippines. - Liongson, Leonardo Q.
This paper reports the general findings of a research project for stochastic modeling and forecasting of monthly and five day inflows to the multi-purpose Angat reservoir. The stochastic models investigated were the pure runoff autoregressive moving average (ARMA) types, both of seasonal and nonseasonal forms, and either with or without state estimation techniques or Kalman filtering; and rainfall runoff ARMA type or ARMAX (ARMA with exogenous input). The research demonstrated the applicability of the best selected models for forecasting dry season low flows and wet season moderate flows. Recommendations for possible model improvements were also made.